Carbon Composites for a High‐Energy Lithium–Sulfur Battey with a Glyme‐Based Electrolyte. Issue 1 (9th November 2016) - Carbone, Lorenzo; Peng, Jing; Agostini, Marco; Gobet, Mallory; Devany, Matthew; Scrosati, Bruno; Greenbaum, Steve; Hassoun, Jusef
Abstract: A comparative study of sulfur composites using carbon of various natures, namely, graphite, mesocarbon microbeads, and multi‐walled carbon nanotubes, is performed in lithium battery design and evaluation. Morphological and structural analyses, by means of SEM and XRD, cyclic voltammetry and galvanostatic cycling in lithium cells are employed for characterization of the materials. Tetraethylene glycol dimethyl ether containing lithium trifluoromethansulfonate is considered the preferred electrolyte for performing the electrochemical tests. Prior to use in cells, the electrolyte characteristics in terms of 1 H, 7 Li, and 19 F nuclei self‐diffusion coefficients, ionic conductivity, and ionic association degree are studied by combining NMR and impedance spectroscopy. The best lithium–sulfur composite reported herein achieves a capacity higher than 500 mAh g −1 over 140 cycles with no sign of dendrite formation or failure. This performance is considered sufficiently suitable for the development of high‐energy lithium batteries, in particular, considering the expected safety of the cells by employing a nonflammable glyme electrolyte instead of a conventional carbonate‐based one. Abstract : Maximizing performance : Carbon composites of various morphologies are successfully studied for application in high‐energy lithium–sulfur batteries that employ a glyme‐based electrolyte (see figure). The study demonstrates differences in the electrochemical behavior of the sulfur–carbon composites, owing to differing reaction kinetics that are directly affected by the electrode structure and morphology.